ANALISIS DEGREE OF OPERATING LEVERAGE (DOL) ATAS PENGGUNAAN AKTIVA TETAP PADA KUD SUPER NEGERI LILIBOOY. - Rahabeat, Nicodemus (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
This study aims to find out whether the Super Village Unit Cooperative is able to cover depreciation costs on the use of fixed assets and to find out whether by using operating leverage analysis the cooperative is able to generate profits.To test the hypothesis taken, the analytical tool used is the degree of operating leverage (DOL) analysis.The results of the analysis show that cooperatives have not been able to achieve a level of efficiency, because the resulting level of operating leverage shows an increase in the first two years and has decreased in the last year. KEY WORDS : DOL, fixed assets and depreciation.